Pengaruh Pendidikan, Pekerjaan, Status Perkawinan, Dan Pendapatan Terhadap Pemberian Dana Bantuan Covid-19 Di Kelurahan Panjang Kota Magelang: (Menggunakan Data Regsosek dan Monografi Kependudukan Kelurahan Panjang 2021) - Nabila Sekar Oktavianti; Nathania Aisha Aufahayu; Gilang Surya Ramadhan; Adella Endah Lathifa (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
This study aims to analyze the effect of education, employment, marital status, and income on the provision of Covid-19 aid funds in Panjang Village, Magelang City. In this study using qualitative methods with technical analysis in the form of probit and logit functions. The data used in this study are secondary, namely population research and monograph data originating from Panjang Village, Magelang City for the 2021 period. In this study, the granting of grants variabel is used as the dependent variabel and the independent variabels are education, employment, marital status, and income. . The results of this study indicate that the marital status variabel has a partial effect on recipients of Covid-19 assistance, while other variabels have no partial effect on Covid-19 assistance. This study shows that the marital status variabel has a positive and significant effect on beneficiaries of aid funds, while the variabels of education, employment, and income have a negatif and insignificant effect on recipients of sosial assistance funds.